2023
DOI: 10.1186/s40545-023-00515-6
|View full text |Cite
|
Sign up to set email alerts
|

Prescribing pattern of antibiotics by family physicians in primary health care

Abstract: Purpose Irrational prescription of antibiotics is an ongoing global public health concern, leading to antibiotic resistance. Understanding the prescribing pattern of antibiotics is important to tackling mal-prescription and antibiotic resistance. We aimed to investigate the pattern and factors affecting outpatients’ antibiotic prescribing by family physicians in Primary Health Care (PHC). Methods A cross-sectional study was conducted in 19 PHC faci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…The senior and more clinical experienced physicians with higher professional degrees had higher control towards antibiotic prescription Regular conferences, workshops, and continuing medical education are used to train physicians to expand their knowledge Tang, et al [ 59 ] Public reporting can positively influence antimicrobial prescribing patterns of doctors particularly for acute respiratory tract infections in primary health care settings, with reduction in the prescription rate of antibiotics and use of antibiotics Public reporting intervention with special concentration on the physician prescription patterns Rodrigues, et al [ 60 ] Working in the emergency department, workload, and physicians’ attitudes were identified as critical factors affecting antibiotics prescriptions Junior doctors' knowledge and clinical behaviour should be improved, and decision-makers should be made aware of the connection between higher workload and subpar performance when prescribing antibiotics Al-Homaidan and Barrimah [ 61 ] Physicians have some shortage of knowledge and attitude about antibiotics regarding beneficial effects of antibiotics, the efficacy of alternatives to antibiotics, antibiotic resistance, harmful effects of antibiotics, practice guidelines, and the advice that should be given to patients who are prescribed antibiotics The adoption of practice guidelines, bettering patient awareness and education, and rules for prescription and dispensing antibiotics are some of the more targeted treatments that primary healthcare providers need Frost, et al [ 62 ] Knowledge deficits regarding current guidelines, specialities and peer prescribing habits, experience, confidence level treating patient and parent factors were main barriers for antibiotic prescription. Additionally, diagnostic uncertainty is a leading driver of antibiotic prescribing To focus Antibiotic Stewardship Program efforts; research on the knowledge, attitudes, and beliefs influencing prescribing practices can be useful Karimi, et al [ 63 ] Study of experience, cultural and societal characteristics, and belief in the significant impact of antibiotic prescription. Self-medication, as well as the people's habits and cultural elements as a whole, encourage them to recommend doctors who frequently prescribe antibiotics There is a need to increase family doctors' knowledge and proficiency in prescription antibiotics in the primary healthcare setting Huang, et al [ 64 ] Diagnostic uncertainty and knowledge gaps, Organizational-related factors (organization norms and culture) were determinants of antibiotics prescribing practices …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The senior and more clinical experienced physicians with higher professional degrees had higher control towards antibiotic prescription Regular conferences, workshops, and continuing medical education are used to train physicians to expand their knowledge Tang, et al [ 59 ] Public reporting can positively influence antimicrobial prescribing patterns of doctors particularly for acute respiratory tract infections in primary health care settings, with reduction in the prescription rate of antibiotics and use of antibiotics Public reporting intervention with special concentration on the physician prescription patterns Rodrigues, et al [ 60 ] Working in the emergency department, workload, and physicians’ attitudes were identified as critical factors affecting antibiotics prescriptions Junior doctors' knowledge and clinical behaviour should be improved, and decision-makers should be made aware of the connection between higher workload and subpar performance when prescribing antibiotics Al-Homaidan and Barrimah [ 61 ] Physicians have some shortage of knowledge and attitude about antibiotics regarding beneficial effects of antibiotics, the efficacy of alternatives to antibiotics, antibiotic resistance, harmful effects of antibiotics, practice guidelines, and the advice that should be given to patients who are prescribed antibiotics The adoption of practice guidelines, bettering patient awareness and education, and rules for prescription and dispensing antibiotics are some of the more targeted treatments that primary healthcare providers need Frost, et al [ 62 ] Knowledge deficits regarding current guidelines, specialities and peer prescribing habits, experience, confidence level treating patient and parent factors were main barriers for antibiotic prescription. Additionally, diagnostic uncertainty is a leading driver of antibiotic prescribing To focus Antibiotic Stewardship Program efforts; research on the knowledge, attitudes, and beliefs influencing prescribing practices can be useful Karimi, et al [ 63 ] Study of experience, cultural and societal characteristics, and belief in the significant impact of antibiotic prescription. Self-medication, as well as the people's habits and cultural elements as a whole, encourage them to recommend doctors who frequently prescribe antibiotics There is a need to increase family doctors' knowledge and proficiency in prescription antibiotics in the primary healthcare setting Huang, et al [ 64 ] Diagnostic uncertainty and knowledge gaps, Organizational-related factors (organization norms and culture) were determinants of antibiotics prescribing practices …”
Section: Resultsmentioning
confidence: 99%
“…Chem, et al [ 54 ] reported that complacency, fear, and insufficient knowledge were other factors that influenced the prescribing of antibiotics by physicians. Kumar, et al [ 44 ] and Karimi, et al [ 63 ] stated that knowledge, skills and insights acquired through interaction with patients and medical cases were associated with physicians’ prescription practices and decisions to prescribe antibiotics.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations